2019
DOI: 10.5812/jjcdc.86864
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer in Isfahan Province, Iran; Prevalence and Demographic Characteristics

Abstract: Background: Previous studies confirm that thyroid cancer, as the most common endocrine cancer, accounts for about 1% of new malignant diseases all over the world. Objectives: As thyroid cancer incidence in Iran has changed rapidly over the past years, therefore this study was designed to investigate period prevalence (PP) and incidence rate (Irs.) of thyroid cancer in Isfahan Province, Iran. Methods: Recorded data of thyroid cancer were obtained from the Isfahan Cancer Registry at the Deputy of Health. Continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The results of this study showed that urinary bladder, kidney cancer followed an increasing trend in incidence, mortality and prevalence in Isfahan, Iran (14)(15)(16)(17)(18)(19)(20)(26)(27)(28)(29)(30)(31)(32). The implications of this investigation could be mentioned as the following suggestions: (1) the health care system should provide a model-based strategy to improve access to specialized medical, pharmacological and surgical facilities; (2) consideration is needed toward the reality for scheduling health system improvements, particularly referral systems; (3) preventing significant difficulties by equality of management for patient satisfaction; (4) attention toward financial management by study of epidemiology and pharmacotherapy.…”
Section: Discussionmentioning
confidence: 69%
“…The results of this study showed that urinary bladder, kidney cancer followed an increasing trend in incidence, mortality and prevalence in Isfahan, Iran (14)(15)(16)(17)(18)(19)(20)(26)(27)(28)(29)(30)(31)(32). The implications of this investigation could be mentioned as the following suggestions: (1) the health care system should provide a model-based strategy to improve access to specialized medical, pharmacological and surgical facilities; (2) consideration is needed toward the reality for scheduling health system improvements, particularly referral systems; (3) preventing significant difficulties by equality of management for patient satisfaction; (4) attention toward financial management by study of epidemiology and pharmacotherapy.…”
Section: Discussionmentioning
confidence: 69%
“…We found that below 55 years old comprising (84.0%) of the total sample. According to previous literature, the occurrence of TC is considered to be much more in the age below 55 years old ,like what Ghamari (2019) published [18]. The explanation of young age group involvement in TC may be due to poor diet or iodine deficiencies in our environment.…”
Section: Discussionmentioning
confidence: 83%
“…Concerning the age distribution of the present study, it is observed that most of the patients with thyroid carcinoma have the age range of (20-60) years, these results are in accordance with the studies of other researchers Calangiu et al (2014). Who found the most positive case is in age group more than 45 years, through analysis of clinicopathological parameters of the 43 thyroids differentiated carcinomas and Ghamari (2019) show an increasing trend in the number of patients recently with a minimum age of three-years-old, in 84% of the patients, the age ranged from 20 to 60 years old in Iran.…”
Section: Discussionmentioning
confidence: 97%